High‐resolution radar measurements of snow avalanches. Issue 4 (28th February 2013) - Vriend, N. M.; McElwaine, J. N.; Sovilla, B.; Keylock, C. J.; Ash, M.; Brennan, P. V.
Abstract : [1] Two snow avalanches that occurred in the winter 2010–2011 at Vallée de la Sionne, Switzerland, are studied using a new phased array FMCW radar system with unprecedented spatial resolution. The 5.3 GHz radar penetrates through the powder cloud and reflects off the underlying denser core. Data are recorded at 50 Hz and have a range resolution better than 1 m over the entire avalanche track. We are able to demonstrate good agreement between the radar results and existing measurement systems that record at particular points on the avalanche track. The radar data reveal a wealth of structure in the avalanche and allow the tracking of individual fronts and surges down the slope for the first time. Key Points: Validation between our radar results and existing point measurement systems High‐resolution radar allows tracking of fronts and surges from start to finish Velocity linked with topography may be used to measure rheology of snow